Life cycle assessment of ceramic façade material and its comparative analysis with three other common façade materials. (15th July 2015) - Han, Baolong; Wang, Rusong; Yao, Liang; Liu, Hongxiao; Wang, Zhonghang
Abstract: Ceramic panels are an emerging construction material and have become popular in China due to the regenerative character of the material and its conformation with Chinese culture. In this paper, we conducted a life cycle assessment (from "cradle" to "grave") of decorative ceramic façade panel products from a typical ceramic enterprise in South China. Both the sales aspect and material recycling were considered. Using Ebalance software and its Chinese parameters, we assessed seven environmental impacts of the ceramic panels, including depletion of abiotic resources, photochemical oxidant creation, global warming, acidification, eutrophication, ozone depletion and human toxicity. We also compared the environmental performance of ceramic façade panels with three other traditional curtain wall materials—glass, marble and aluminum plate—using data from the literature. The results from a consideration of the life cycle from "cradle" to "gate" showed that ceramic façade panels had better environmental performance than the others, in general, but was worse than glass on the depletion of abiotic resources performance and was worse than glass and aluminum on the human toxicity performance. Finally, we offer some suggestions for optimizing the life cycle process of ceramic façade panels for better environmental performance and some recommendations for better selection of façade materials. Highlights: This was an original LCA research on ceramic façade panel, which is widely used around the world. Environmental impact of ceramic and other three façade materials were compared by literature review. The LCA data was collected by field investigation in an typical ceramic panel factory. This research included sales section, which was often overlooked by previous LCA research. According to the LCA result ecological adjustment and recommends for façade materials selection were made.